If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -7) = 6(x + -4) Reorder the terms: 8(-7 + x) = 6(x + -4) (-7 * 8 + x * 8) = 6(x + -4) (-56 + 8x) = 6(x + -4) Reorder the terms: -56 + 8x = 6(-4 + x) -56 + 8x = (-4 * 6 + x * 6) -56 + 8x = (-24 + 6x) Solving -56 + 8x = -24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -56 + 8x + -6x = -24 + 6x + -6x Combine like terms: 8x + -6x = 2x -56 + 2x = -24 + 6x + -6x Combine like terms: 6x + -6x = 0 -56 + 2x = -24 + 0 -56 + 2x = -24 Add '56' to each side of the equation. -56 + 56 + 2x = -24 + 56 Combine like terms: -56 + 56 = 0 0 + 2x = -24 + 56 2x = -24 + 56 Combine like terms: -24 + 56 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| 3x^2-5+1=0 | | 2x+108=8x+60 | | 3x+12y=-30 | | -7x+5(8+9n)=4(9n+1) | | -(7x+3)-(5x-3)=7-(2x+1) | | 2Y=3X-Y | | 3(-2)-1=-2-5 | | 3x+41=65 | | 12(-2b-12)=-6(-3b+10) | | -2x+1=3x-9 | | -5x=-2x-6 | | 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a |